Driver adaptation to information and assistance systems - Stevens, A. (Researcher in transportation); Brusque, Corinne; Krems, Josef (Institution of Engineering and Technology, 2014)
Driver information and assistance systems have emerged as an integral part of modern road vehicles in order to support the driver while driving.
Keywords: Driver assistance systems.; Motor vehicles -- Technological innovations.; Motor vehicle drivers -- Attitudes.; Motor vehicle driving.; Automobile driving.; Automobile driving -- Steering.; elektronické knihy; electronic books